2021
DOI: 10.1097/scs.0000000000007748
|View full text |Cite
|
Sign up to set email alerts
|

Objective Analysis of Fronto-Orbital Dysmorphology in Unilateral Coronal Craniosynostosis

Abstract: Correction (and over-correction) of asymmetries of the orbital shape and brow position in unilateral coronal craniosynostosis (UCS) is critical to successful fronto-orbital advancement.Here we quantify and three-dimensionally assess fronto-orbital irregularities in UCS patients compared to controls.Twenty-three patients with UCS evaluated at the Children's Hospital of Pittsburgh between 2006 and 2016 were age and gendermatched to controls. Computed tomography scans were reconstructed and evaluated for orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In the vast majority of nonsyndromic craniosynostosis, a single skull remodelling procedure is sufficient, but it has to be performed in ideal intervals of time. For scaphocephaly the ideal age for surgery in our experience was between three and six months of age [3,15,16]. By performing the procedure so early, the brain has enough growth potential to shape the skull on its own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vast majority of nonsyndromic craniosynostosis, a single skull remodelling procedure is sufficient, but it has to be performed in ideal intervals of time. For scaphocephaly the ideal age for surgery in our experience was between three and six months of age [3,15,16]. By performing the procedure so early, the brain has enough growth potential to shape the skull on its own.…”
Section: Discussionmentioning
confidence: 99%
“…The frontoorbital advancement (FOA) is used for metopic and coronal craniosynostosis [12][13][14] and the posterior vault expansions for lambdoid craniosynostosis [6,7]. Biparietal or total cranial vault remodelling techniques are used in scaphocephaly [3,15,16]. In syndromic cases, Chiari malformation, intracranial hypertension, hydrocephalus and central or peripheral apneas are often present and must be considered during the planning of the correct treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies observed side-to-side asymmetry in orbital volume, with the volume on the ipsilateral side being significantly lower than the volume on the contralateral side. 3,8,16,[18][19][20] Different authors used their preferred orbital boundaries when segmenting the orbital cavity to calculate the volume. In this study, the anterior boundary of the orbit was defined as the inner surface of the eyelid (Fig.…”
Section: Morphometry Of the Orbitsmentioning
confidence: 99%
“…Since Calandrelli et al3 classified their patients using the Di Rocco and Velardi15 classification scheme, they found a steady decrease in the volume on the ipsilateral orbits as the severity of ASP increased. Dvoracek et al8 reported on orbital height and breadth—they found that the height significantly increased, and the breadth significantly decreased on the ipsilateral orbit. Marsh et al17 and Mesa et al21 found that the SOR of the ipsilateral orbit was higher than the SOR of the contralateral orbit.…”
mentioning
confidence: 99%
See 1 more Smart Citation